Strategi Peningkatan Kualitas Ruang Terbuka Hijau Publik Di Kabupaten Gowa (Studi Kasus :Syekh Yusuf Discovery): CASE STUDY : SYEKH YUSUF DISCOVERY - Anugrah, Rahmi; Manaf, Murshal; Taking, Muh. Idris (Fakultas Teknik Universitas Bosowa, 2023)
This study aims to analyze the quality of Public Green Open Space in Syekh Yusuf Discovery based on visitor perceptions and formulate a strategy to improve the quality of Public Green Open Space in Syekh Yusuf Discovery. The research method used is quantitative method. The technical analysis used is quantitative descriptive analysis using Likert scale and SWOT analysis. The results showed that the quality of Syekh Yusuf Discovery's Public Green Open Space based on ecological functions obtained a poor quality value. The socio-cultural function acquires good quality values. The water catchment function obtained a poor quality value. The economic function acquires a good quality value. Then the aesthetic function acquires excellent quality values. The improvement of the quality of Syekh Yusuf Discovery's Public Green Open Space can be done by maintaining its function as a pollution absorber and noise absorber to minimize air pollution, maintaining the function of green open space as a means of interaction, sports, creativity and education / training to anticipate changes in land function and increasing public understanding of the importance of green open space so as to create comfort and beauty Changing land functions and increasing public understanding of the importance of green open space so as to create comfort and beauty of the environment.